Comparative on AODV and DSR under Black Hole Attacks Detection Scheme Using Secure RSA Algorithms in MANET - Jamgade, Meenakshi; Shukla, Vimal (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc Network (MANET) is a new field of communication operating in an extremely unpredictable and dynamic environment. These networks are gaining increasing popularity in recent years because of their ease of deployment. A MANET consists of collection of wireless mobile nodes that are capable of communicating with each other without the use of any network or any centralized administration. In ad hoc networks, routing protocols are challenged with establishing and maintaining multi-hop routes with security in the face of mobility, bandwidth limitation and power constraints. In particular in MANET, any node may be compromise the routing protocol functionality by disrupting the route discovery process. To achieve broad protection and desirable network performance, routing security is unavoidable. In this research work, a secure routing protocol for MANET is designed with the countermeasures to reduce or eliminate different types of security vulnerabilities and attacks. This paper provides routing security to the Ad hoc on demand Distance Vector (AODV) routing protocol by eliminating the threat of Black Hole attack, Wormhole attack, Rushing attack, and Impersonation attack. The proposed solutions are tested using Network Simulator2 (NS2), a scalable network simulator. The performance is studied for in various routing parameters such as packet delivery ratio, average end - to - end delay and routing overhead and are compared with the AODV and DSR. Hence we have known Cryptographic algorithm such as RSA (Rivest Shamir Adleman) Algorithm is used for providing a secure routing between mobile nodes even in the presence of malicious nodes .In brief, this paper presents a counter measure to overcome Black hole attack.